2023
DOI: 10.3846/jbem.2023.19059
|View full text |Cite
|
Sign up to set email alerts
|

Labour Productivity Analysis of Manufacturing Sector in Turkey Against Eu

Abstract: This study offers an in-depth analysis of labour productivity of manufacturing sector in Turkey and provides a comparison with EU27 and EA19 countries utilizing Eurostat time series data of 63 quarters covering 2005/first quarter-2020/third quarter time interval. Productivity trends are identified and interpreted by relating them with the key macroeconomic events and factors. Multiple linear and non-linear regression equations, and ARIMA model with different parameters are applied to the time series data consi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 73 publications
0
3
0
Order By: Relevance
“…As Bloom et al (2023) reported, the COVID-19 pandemic generally led economies to decline, negatively affecting living standards, public finances and productivity. Balkan & Akyuz (2023) recall the intense deterioration and identify the decline in economic growth and increasing budget deficits of cou ntries as reasons for this. For example, according to an international study, the pandemic, in the context of disrupting the continuity of economic processes, had a significantly negative impact on productivity and labour costs -the cumulative global economic loss amounted to roughly $10.4 trillion in 2020-2022, of which the economic losses of the EU, the US and China amounted to 30.44%, 18.74% and 15.44%, respectively (Cui et al, 2023).…”
Section: Entrepreneurship and Sustainability Issuesmentioning
confidence: 99%
“…As Bloom et al (2023) reported, the COVID-19 pandemic generally led economies to decline, negatively affecting living standards, public finances and productivity. Balkan & Akyuz (2023) recall the intense deterioration and identify the decline in economic growth and increasing budget deficits of cou ntries as reasons for this. For example, according to an international study, the pandemic, in the context of disrupting the continuity of economic processes, had a significantly negative impact on productivity and labour costs -the cumulative global economic loss amounted to roughly $10.4 trillion in 2020-2022, of which the economic losses of the EU, the US and China amounted to 30.44%, 18.74% and 15.44%, respectively (Cui et al, 2023).…”
Section: Entrepreneurship and Sustainability Issuesmentioning
confidence: 99%
“…As Bloom et al (2023) reported, the COVID-19 pandemic generally led economies to decline, negatively affecting living standards, public finances and productivity. Balkan & Akyuz (2023) recall the intense deterioration and identify the decline in economic growth and increasing budget deficits of cou ntries as reasons for this. For example, according to an international study, the pandemic, in the context of disrupting the continuity of economic processes, had a significantly negative impact on productivity and labour costs -the cumulative global economic loss amounted to roughly $10.4 trillion in 2020-2022, of which the economic losses of the EU, the US and China amounted to 30.44%, 18.74% and 15.44%, respectively (Cui et al, 2023).…”
Section: Entrepreneurship and Sustainability Issuesmentioning
confidence: 99%
“…(1976) argued that the quality of an individual's life consists of such components as: marriage, family life, health, neighbors, friends, housework. The most important factors are the availability of work (Kuzior, 2022a;Balkan & Akyuz, 2023;Kuráth et. al., 2023), living conditions in the country (Vasa & Hovhannisyan, 2007;Blažević Bognar & Pleša Puljić, 2022;Altunoğlu et.…”
Section: Literature Reviewmentioning
confidence: 99%